Transplante do epitélio pigmentado da retina derivado de células tronco - embrionárias em modelo animal de grande porte estudos pré-clínicos - Fernandes, Rodrigo Antonio Brant [UNIFESP] (2019)
Objectives: To assess the cell safety, survival and feasibility of the subretinal transplantation of human embryonic stem cell-derived retinal pigment epithelium (hESC-RPE) in Yucatan minipigs and to determine the surgical technique to be used in humans. Also the cell culture methods were replicated in Brazil, and the stem cells derived REP cells were modified to express the fluorescent protein cGMP. Methods: Ultrathin films made from parylene C were seeded with hESC-RPE and implanted in the subretinal space of immunosupressed Yucatan minipigs. Four studies were designed, completed and published. The first study assessed the viability of the surgical procedure and the first version of the tissue injector, along with the correct positioning of the implant. The compatibility of its dimensions with the human eye and the tissue integrity after placement were evaluated through ocular imaging (Optical Coherence Tomography (OCT)) and histological examination (n=8). Three months after implantation, when the animals were sacrificed, adjacent sections were processed for immunohistochemical analysis using TRA-1-85 (human blood group antigen) and DAPI antibodies. In the second study, we reported the evolution of the tissue injector and the implant dimensions using the data gathered in the first study, with its final formats determined for the human clinical trial. We performed acute surgical procedures, along with ocular imaging of the impacted eyes. The animals were sacrificed after the image acquisitions and the eyes were evaluated histologically. In this study, the cell survival and possible tumor formation were evaluated in animals submitted to the implantation of parylene C seeded with ESC-RPE in the final dimensions to be used in the human clinical trial. In the fourth study we described the method for differentiation and enrichment of hESC-RPE in Brazil. Results: In the first study, the RPE monolayer seeded in the parylene C substrate proved positive to TRA- 1-85 and RPE-65 three months after implantation, showing cell viability after this follow-up period without adverse effects. The cells didn’t migrate outside the substrate and there were neither tutor formation locally nor other body tissues or organs. In the second study, the new modifications on the substrate and injector were evaluated in an acute surgical procedure, where the animals were sacrificed immediately after the surgical procedure and ocular image acquisition. There was no tissue damage to the surrounding ocular tissues due to the surgical technique and there was minimal cell loss over the substrate. In the third study, animals were implanted with the final format of the substrate and tissue injector, with a control group receiving only subretinal saline, and were kept immunosuppressed with cyclosporine for one month, and then sacrificed. No adverse events were observed and the cells proved positive to TRA-1- 85 and RPE-65 after one month of follow-up. No difference was found histologically between the implanted animals and the controls. In the fourth study we described the method for differentiation and enrichment of hESC-RPE in Brazil. The method produced a yield of 108 cells, and the cells exhibited all the biomarkers and gene expression of adult RPE cells. Conclusion: The hESC-RPE cells survived for at least three months in this animal model. The surgical procedure and subretinal implantation of the substrate with cells were feasible and safe without migration of the substrate or the induction of tumors in the eyes and organs of the immunosuppressed animals. The method for differentiation and enrichment proved reliable and replicable, with the cells expressing the biomarkers of adult RPE cells.